Effectiveness of the Hong Kong convention on ship recycling in India, Bangladesh and Pakistan - Ali, Mohammad; Pearce, Prafula (Copyright Publishing Co. Pty Ltd, 2020)
Ship recycling or shipbreaking is the process of breaking up old ships mainly for their steel. International shipping companies own and use ships for their trade and ultimately sell them predominantly to Bangladesh, India, and Pakistan (South Asian Countries) for breaking up. As they have no iron ore to support their growing steel demand, these South Asian countries can offer attractive prices to shipowners. The activities in South Asian countries occur on open beaches using dangerous manual methods to save cost that actually pollute the environment, and cause deaths and injuries to workers in the ship recycling or shipbreaking industry. Considering the global nature of the problem, the International Maritime Organisation (IMO) in 2006 decided to frame a comprehensive legally binding regime for regulating risks associated with ship-breaking activities.1 Subsequently, the Convention for the Safe and Environmentally Sound Recycling of Ships (the Hong Kong Convention) was adopted at a diplomatic conference held in May 2009 in Hong Kong.2 Prior to this, the only applicable international convention was the Basel Convention on the Control of Transboundary Movement of Hazardous Waste and their Disposal, 1989 (the Basel Convention). This article explains the deficiencies of the Basel Convention, explores the effectiveness of the Hong Kong Convention, and examines whether it has improved the shipbreaking practices in South Asia’s developing countries. The article also evaluates the Hong Kong Convention’s ability to regulate inter-State movement of contaminated ships in order to determine whether the ‘cradle to grave’ approach introduced by the Convention is sufficient to protect the marine environment and rights of workers at the recycling or shipbreaking facilities in the South Asian countries.